Trends in paediatric acute asthma management in the republic of Ireland: a comparison between community and hospital practice. (24th May 2012) - Cronin, J; McCoy, S; Pollock, J; Breen, N; Walsh, S; O'sullivan, R
Abstract : Aims: The prevalence of childhood asthma in Ireland is amongst the highest in the world. Evidence-based guidelines for the management of acute paediatric asthma have been shown to improve care in a variety of centres internationally. The authors are anecdotally aware of varying practices in management of this condition in different healthcare settings. We aim to compare the management of this condition by Emergency Physicians (EPs), Paediatricians and community-based General Practitioners (GPs). Methods: A standardised online anonymous survey was conducted of senior EPs, Paediatricians and General Practitioners (GPs) in Ireland. 15% of GPs nationally were chosen using a computerised randomisation method. Those GPs for whom an email address was available were surveyed online, otherwise a postal form of the survey was sent out. Results: We received 263 responses, giving a response rate (RR) of 40.6% (EP: 44/71, RR=62.0%; Paediatricians: n=69/160, RR=43.1%; GP: n=154/427, RR=36.1%). There was a significant difference between the specialities in the use of guidelines and discharge asthma action plans (table 1 ). Over 70% of paediatricians and EPs use spacer devices for mild and moderate attacks. 78% of GPs use spacers for mild attacks, however this drops to 38% for moderate. Paediatricians and EPs differed in their choice of first line IV bronchodilators with paediatricians choosing salbutamol (48.3%) most frequently and EPs choosing magnesium (48.3%). Whereas almost all respondents felt that severe attacks should be referred to an ED, over 85% of paediatricians and EPs felt that moderate attacks should be referred compared to 13.7% of GPs. Over 90% of all respondents would welcome a national guideline on the management of acute paediatric asthma exacerbations. Conclusion: This is the first study of its kind internationally to compare management of this important and common condition across the 3 relevant specialties. The results of this survey support the development of a national guideline for acute paediatric asthma management.